Plasma protein binding monitoring of therapeutic drugs in patients using single set of hollow fiber centrifugal ultrafiltration. (April 2017) - Wang, Xinyu; Li, Cen; Du, Chaohui; Gao, Jing-lin; Zhao, Ke-Xin; Shi, Rui; Jiang, Ye
Aim: Plasma protein binding (PPB), as a significant influenced factor of pharmacokinetic and pharmacodynamic properties of a medicine, is a suitable index for therapeutic drug monitoring (TDM) strategies. A suitable measurement technique of PPB of patients is in urgent need and attracts many analysts' attention.Results & methodology: In this study, a novel method was proposed to analyze free drug concentration and total drug concentration (Ct ) successively in one unit with a sample. All RSDs were less than 3%. The absolute recovery of Ct ranged from 98.1 to 101.2%.Discussion & conclusion: It is extremely valuable to consider PPB as an important index for TDM, perfecting information of medication, reflecting the disease condition more comprehensively, providing assistance for doctors to adjust the dose regimen. The proposed technique, convenience, accuracy and without the influence of plasma condition, provides a feasible method to monitor PPB of various patients, facilitating the popularization of monitoring PPB in TDM.